Blended Learning Method to Optimize English Language Learning in Non-English Language Education Departments at Muhammadiyah University of Enrekang - Rahman, Musdalifah Ifah; Ismaya, Ismaya (Universitas Muhammadiyah Enrekang, 2021)
Limited time to direct learning in class often made learning English less effective, especially for classes with various levels of English proficiency. In a higher education climate that demands active learning, English teachers often find it difficult to help students whose English competency was below average to catch up with their peers who had good competence. In general, this compulsory course was only held for one semester. In fact, the target of learning English on campus was generally quite high, namely to make students had sufficient English proficiency so that they could write academic papers in English as an international language. To help overcome these obstacles, this study offers the use of the blended language learning method, which was a learning method that complements direct learning with distant learning using the internet. Blended language learning was able to complement the lack of direct time in class with distance learning using internet media. This research was the result of writer's experience in applying this method for one academic year along with the results obtained from the application of the blended language learning method in the teaching process. With the application of the blended language learning method, the writer found that language learning at the college level could be more effective, efficient, and more student-centered even though the author still faces some obstacles in its application.